2020
DOI: 10.1002/jclp.22939
|View full text |Cite
|
Sign up to set email alerts
|

Lower intimate relationship satisfaction among partnered female service members/veterans is associated with the presence of suicidal ideation

Abstract: Objectives: Risk for suicide among female service members/veterans (SM/Vs) is increasing, suggesting a need for additional studies of risk factors in this population. This study examined relationship satisfaction as a correlate of suicidal ideation (SI) after accounting for established risk factors for SI. Method: Partnered female SM/Vs (N = 818) completed a demographic inventory and measures of SI, relationship satisfaction, sexual function, posttraumatic stress disorder (PTSD), and depression.Results: After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(47 reference statements)
1
6
0
1
Order By: Relevance
“…Cognitive function is associated with activities of daily living and age. Similiar to other studies, the present study also showed that the number of needs was higher in groups with older age 16,30 . It is pointed out that older adults living at home were two‐ to fivefold more likely to be disadvantaged members, and 93.1% of disabled older people had at least one unmet need 12 .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Cognitive function is associated with activities of daily living and age. Similiar to other studies, the present study also showed that the number of needs was higher in groups with older age 16,30 . It is pointed out that older adults living at home were two‐ to fivefold more likely to be disadvantaged members, and 93.1% of disabled older people had at least one unmet need 12 .…”
Section: Discussionsupporting
confidence: 73%
“…On the contrary, spouses have more opportunities to provide company for care recipients and undertake additional caregiving tasks, thus reducing the loneliness of care recipients and having a positive impact on their overall health 9 . Research found that having a caregiver who was willing to provide services reduced the risk of having unmet needs by 77% 30 . However, the caregiving tasks make spouses experience more depression and less well‐being 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, civilian research shows that the prevalence rate for PTSD among females is higher than the prevalence rate observed in males (see reviews, Brewin, Andrews, & Valentine, 2000; Ditlevsen & Elklit, 2012; Greene, Neria, & Gross, 2016; McLean & Anderson, 2009; Tolin & Foa, 2006), which may be due, in part, to having a higher likelihood of exposure to sexual violence (Frans, Rimmö, Åberg, & Fredrikson, 2005; Perrin et al, 2014). Finally, satisfying romantic relationships can buffer against suicidal ideation (e.g., Blow, Ganoczy, Walters, & Valenstein, 2018) and psychological distress (e.g., Taft et al, 2011), and emerging data reveals that among female SM/Vs, poorer relationship satisfaction is associated with increased suicide risk above and beyond the effects of PTSD and depression (Blais, 2019a). These studies highlight the critical need to further understand the association of PTSD symptom clusters and relationship satisfaction in females.…”
Section: Introductionmentioning
confidence: 99%
“…Sonuçlar, İDİ-4'ün oldukça güvenilir olduğunu göstermiştir (Çokluk ve diğ., 2010). Benzer bir biçimde, önceki çalışmalarda da (örn., Blais, 2020;Funk ve Rogge, 2007;Lamela, Figueiredo, Morais, Matos ve Jongenelen, 2020) İlişki Doyum İndeksi için yüksek güvenirlik katsayısı rapor edilmiştir. Son olarak, çoklu grup doğrulayıcı faktör analizi sonuçları, İDİ-4'ün faktör yapısının ve yüklerinin medeni duruma göre anlamlı bir farklılık göstermediğini, başka bir deyişle, ölçme değişmezliğine sahip olduğunu göstermiştir.…”
Section: İdi̇-4 öLçme Değişmezliğine İlişkin Bulgularunclassified